Numerical simulations of stiffened multi-arch double-layered panels subjected to blast loading - Chen, Wensu; Hao, Hong (Multi-Science Publishing, 2013)
Blast-resistant structures are traditionally designed and fabricated with solid materials of heavy weight to resist blast loadings. This not only increases the material and construction costs, but also undermines the operational performance of protective structures. To overcome these problems, new designs with either new structural forms or new materials are demanded against blast loads. A multi-arch double-layered panel has been proposed as a new structural form in a previous study [1]. Its performance has been numerically demonstrated better than other forms of double-layered panels in resisting blast loads. In this study, to further improve the effectiveness of the multi-arch double-layered panel in resisting blast loads, responses of a five-arch double-layered panel with rectangular stiffeners to detonations are investigated by using finite element code Ls-Dyna. The numerical results show that the stiffened panel outperforms the unstiffened panel of the same weight in terms of the blast-resistant capacity and energy absorption capacity. Parametric studies are conducted to investigate the effects of various stiffener configurations, boundary conditions, stiffener dimension, strain rate sensitivity and blast intensity on the dynamic response to blast loadings. The central point displacements, internal energy absorptions, boundary reaction forces and plastic strains are compared and the optimal configurations of blast-resistant panel are determined. It demonstrates that the strategic arrangement of stiffeners with appropriate boundary conditions can maximize the reduction of dynamic response of the panels to blast loadings. The stiffened multi-arch dotuble-layered panels have great application potentials in the blast-resistant panel design.